Моделирование и анализ переходных процессов в электрических цепях полупроводниковых электроразрядных установок с нелинейной электроискровой нагрузкой - Супруновская, Наталия Игоревна (НТУ "ХПИ", 2014)
Исследованы циклические переходные процессы в зарядно-разрядных цепях конденсаторов полупроводниковых генераторов разрядных импульсов с применением математической модели сопротивления нелинейной электроискровой нагрузки, зависящего от величины разрядного тока, скорости его изменения и длительности временной паузы между разрядными импульсами. Проведен анализ путей повышения динамических характеристик импульсных токов в электроискровой нагрузке, возникающих при регулировании режимов разряда накопительных конденсаторов генераторов разрядных импульсов.

The cyclic transients in charge-discharge circuits of capacitor of semiconductor generators of discharge pulses (GDP) using of mathematical model of resistance of the nonlinear electro-spark load, depending on discharge current, rate of its change and duration of the pause time between discharge pulses are studied. The considered model also takes into account that the load resistance can have different values at the beginning and end of the capacitor discharge and changes during the pause between the discharge pulses. The analysis of ways to improve the dynamic characteristics of pulse currents in the electro-spark load, arising during control of discharge condition of GDP's reservoir capacitors is carried out. The comparative analysis of time-varying characteristics of capacitor discharge circuit (electric resistance of electro-spark load, the voltage drop on it, the rate of rise of discharge currents and power consumed in the load) at modeling of electro-spark load by linear and nonlinear electric resistance is carried out.
Modeling and transient analysis in electric circuits of semi-conductor electro-discharge installations with nonlinear electro-spark load
Keywords: разряд; конденсатор; импульс; модель математическая; сопротивление нелинейное; discharge; capacitor; pulse; electro-spark load; transients; mathematical model; nonlinear resistance